Telling without talking: dynamic products' potential for non-verbal communication. (2016) - Colombo, Sara; Rampino, Lucia
Product semantics has, for decades, been studying how products' sensory features convey implicit messages to users. Now, thanks to advances in technology, static product features, such as shape, texture, colour and smell, are becoming dynamic, actively changing over time. These new properties may be employed to communicate dynamic information to users. Exploring how this sensory communication is accomplished and what potential and limitations dynamic products bring is the aim of this paper. To this end, case studies were analysed and users were interviewed. Results show that dynamic products can convey messages to users, enhancing user experience by making communication more effective and engaging. However, users pointed out limits for interacting with these products. This work represents a starting point in the exploration of an emerging scenario for products' communication with users.